The burden for knee osteoarthritis among Chinese elderly: estimates from a nationally representative study - Liu, Q.; Wang, S.; Lin, J.; Zhang, Y. (Osteoarthritis and cartilage, 2018)
To estimate the burden of knee osteoarthritis (OA) among Chinese population. Individuals with symptomatic knee OA based on self-reported physician-diagnosed arthritis and presence of knee pain were identified in China Health and Retirement Longitudinal Study. Severity of knee OA was divided into three categories: mild, moderate and severe, according to knee pain severity. We estimated sex-specific years lived with disability (YLD) and YLD rate (per 100,000 population) by multiplying the prevalence of knee OA with appropriate disability weight (DW) and examined associations between several key sociodemographic factors and YLDs. Among 17,459 subjects (52.1% women; mean age 59.1 years) included in this analysis, prevalence of mild, moderate and severe knee OA was 1.5%, 3.3%, and 3.9%, respectively. The total number of YLDs for knee OA in China was 4,149,628, and YLDs per 100,000 population was 968. Female sex, older age, rurality, lower education, and lower gross domestic production (GDP) per capita were associated with high YLDs rates for knee OA, respectively. The North and East regions of China had the lowest YLD rate per 100,000 population for knee OA (631 and 699), followed by South-central (858), Northeast (878), and Northwest (1502) regions. Southwest region had the highest YLD rate from knee OA (1653). In this nationally representative sample, we demonstrated a high burden from knee OA among Chinese population. YLD rate for knee OA varied significantly according to sociodemographic factors. Our study calls for an urgent need for health policy support and cost-effective preventive strategies in China.